Balancing opportunity and conflict: the impact of a refugee influx on the decentralisation process - Blaser, Caitlin (My University, 2009)
Abstract This study explores the impact a refugee influx has on the decentralisation process. It uses the case study of Loulouni, southern Mali, in 2005-2006, where a camp for Ivorian refugees was established. Using mixed methods including a large survey and many in depth interviews, this study has found that the refugee influx has had a profound and transformatory impact on decentralisation at the local level. In Mali, the decentralisation effort is closely tied to the promotion of participatory democracy in the country, and the refugee presence has further promoted interaction between citizens and local government officials. However, the arrival of resources in the form of humanitarian aid has also caused conflict between upwardly and downwardly accountable local government authorities, which threaten a complete transfer or powers.